2013
DOI: 10.1051/0004-6361/201220769
|View full text |Cite
|
Sign up to set email alerts
|

Radio polarimetry of compact steep spectrum sources at sub-arcsecond resolution

Abstract: Aims. We report new Very Large Array (VLA) polarimetric observations of compact steep-spectrum (CSS) sources at 8.4, 15, and 23 GHz. Methods. Using multi-frequency VLA observations we have derived sub-arcsecond resolution images of the total intensity, polarisation, and rotation measure (RM) distributions.Results. We present multi-frequency VLA polarisation observations of CSS sources. About half of the sources are point-like even at the resolution of ∼0.1 × 0.1 arcsec. The remaining sources have double or tri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Furthermore, images of some GPS sources show distorted morphologies and the presence of dust, suggesting that mergers and galaxy-galaxy interaction played an important role in these objects [2,3,24,25]. This corroborates the hypothesis that some CSS sources are confined in the dense nuclear region.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, images of some GPS sources show distorted morphologies and the presence of dust, suggesting that mergers and galaxy-galaxy interaction played an important role in these objects [2,3,24,25]. This corroborates the hypothesis that some CSS sources are confined in the dense nuclear region.…”
Section: Introductionsupporting
confidence: 76%
“…[1,2]. They show double, triple and core-jet morphologies on the radio maps [3]. They have steep high frequency spectrum of spectral index, * ≥ 0.5 , , -∝ / [3 and references therein].…”
Section: Introductionmentioning
confidence: 99%
“…Support to the presence of a dense and inhomogeneous medium in front of the radio source comes from the large rotation measure (RM) estimated for those sources with some polarized emission. RM of the order of 1000 rad m −2 or even higher are commonly observed (e.g., O'Dea 1998, Cotton et al 2006, Rossetti et al 2008, Mantovani et al 2013. A different result was found by Mantovani et al (2009) who studied a complete sample of CSS with multifrequency single-dish observations.…”
Section: Polarizationmentioning
confidence: 89%
“…High-resolution imaging (0.1arcsec) with MERLIN revealed that the central radio core breaks up into two components (Akujor et al 1991): a core and jet knot, separated by 0.2arcsec. The radio source has strong spatial radio depolarization inhomogeneity (Mantovani et al 2013). 3C298 is one of the strongest dust emitters in the 3C catalog, with significant Herschel detections at 250, 350 and 500μm (Podigachoski et al 2015).…”
Section: Introductionmentioning
confidence: 99%